2013
DOI: 10.18172/cig.1243
|View full text |Cite
|
Sign up to set email alerts
|

Una revisión de los procesos de sufosión o piping en España

Abstract: RESUMEN. Se revisan los estudios que hacen referencia al desarrollo de pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Muchos de los escarpes aparecen intensamente erosionados, a veces con tendencia al desarrollo de una densa red de cárcavas que conectan con rellenos holocenos a veces afectados por procesos de piping (formación de colapsos por hundimiento de conductos subsuperficiales). Estos procesos erosivos pueden aparecer también en campos de regadío, a condición de que se trate de suelos salinos o con elevado contenido en sodio, dificultando las labores agrícolas (García-Ruiz et al, 1997;García-Ruiz, 2011). Peña-Monné et al (2017) demostraron la rápida y compleja evolución del relieve en el centro de la Depresión del Ebro, debido a la interacción entre fluctuaciones climáticas y actividades humanas.…”
Section: El áRea De Estudiounclassified
“…Muchos de los escarpes aparecen intensamente erosionados, a veces con tendencia al desarrollo de una densa red de cárcavas que conectan con rellenos holocenos a veces afectados por procesos de piping (formación de colapsos por hundimiento de conductos subsuperficiales). Estos procesos erosivos pueden aparecer también en campos de regadío, a condición de que se trate de suelos salinos o con elevado contenido en sodio, dificultando las labores agrícolas (García-Ruiz et al, 1997;García-Ruiz, 2011). Peña-Monné et al (2017) demostraron la rápida y compleja evolución del relieve en el centro de la Depresión del Ebro, debido a la interacción entre fluctuaciones climáticas y actividades humanas.…”
Section: El áRea De Estudiounclassified
“…Also, Ries and Marzolff (2003) in the Ebro Depression, showed fast evolution of badland areas due to pipe dynamics and collapses, resulting in a chaotic morphology. Piping as a subsurface erosion process is still considered one of the most difficult ones to study, and it seems that all investigation leads to its surface being underestimated (Martínez-Casasnovas, 2003;García-Ruiz, 2011). Bernatek-Jakiel and Kondracka (2016) suggested that mapping pipes and collapsed pipes is the most common method of pipe detection.…”
Section: Geomorphological Dynamics: First Approachmentioning
confidence: 99%
“…Traditionally, the development of piping has been associated with the presence of several conditioning factors: climate, physiography, and the inherent properties of soils or sediments (Jones, 1981;Bryan and Yair, 1982;Selby, 1982;Parker et al, 1990;Jones, 1994Jones, , 2004Faulkner et al, 2000, Desir andMarin, 2011;Goudie, 2013 In the central Ebro Basin, soil loss by piping is especially amplified in unconsolidated materials (mainly silts and clays) due to irrigation and the saline nature of the soil (García-Ruiz et al, 1997;García-Ruiz, 2011;Gutiérrez et al, 1997). In the Sariñena Basin, the salinity and sodicity of the soils and Miocene sediments, together with the low organic matter content of the soils (Tables 4 and 5), promote the structural instability and dispersibility of materials and their transport through the subsurface, as well as conspicuous surface soil erosion.…”
Section: The Role Of Piping Processes In the Evolution Of The Basinmentioning
confidence: 99%